2018
DOI: 10.6007/ijarbss/v8-i12/4988
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Environmental Degradation in ASEAN-5

Abstract: This study investigates the relationship between financial development and environmental degradation in ASEAN-5 countries namely Indonesia, Malaysia, Philippines, Singapore, and Thailand over the period of 2000 to 2014. The Panel Unit Root test, Panel Cointegration test, Vector Error Correction Model (VECM) Granger Causality, and Fully Modified Ordinary Least Square (FMOLS) are used in this study to examine the short-run and the long-run as well as the causality relationship among the variables. Variables empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, another strand of literature identified the positive and beneficial effects of financial development on environment quality. Panel studies by Xiong and Qi (2018) covering 30 provinces of China, (Hamdan et al. , 2018), for 5 ASIAN economies and Majeed and Mazhar (2019) for a global panel of 131 countries document the beneficial effect of FD on environment.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, another strand of literature identified the positive and beneficial effects of financial development on environment quality. Panel studies by Xiong and Qi (2018) covering 30 provinces of China, (Hamdan et al. , 2018), for 5 ASIAN economies and Majeed and Mazhar (2019) for a global panel of 131 countries document the beneficial effect of FD on environment.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, another strand of literature identified the positive and beneficial effects of financial development on environment quality. Panel studies byXiong and Qi (2018) covering 30 provinces of China,(Hamdan et al, 2018), for 5 ASIAN economies andMajeed and Mazhar (2019) for a global panel of 131 countries document the beneficial effect of FD on environment. Among time series studies specific to India include;Boutabba (2014) examined the impact of financial development measured by domestic credit to private sector on carbon emissions after controlling for economic growth, energy consumption and trade using autoregressive distributed lag (ARDL) estimator for India covering 1970-2008 time period.…”
mentioning
confidence: 99%
“…Likewise, financial development could enhance economic activities and mass production through capital mobilization, resulting in environmental degradation [28,29]. On the other hand, it could help in improving ecological superiority by channeling monetary resources to eco-friendly schemes [30]. Moreover, the available solutions in the literature are also vague.…”
Section: )mentioning
confidence: 99%
“…Finances could enhance economic activities by reducing credit limits, leading to environmental degradation (Adebayo et al, 2021;Zeqiraj et al, 2020). On the other hand, fi nances could improve environmental quality by redirecting investments into green economic activities (Hamdan et al, 2018). Examined results of a Southeast Asian study revealed that a sustainable environment is in favour of human health and economic growth (S. A. R. Khan et al, 2020b).…”
Section: Literature Reviewmentioning
confidence: 99%